Correlation between criminal procedural legal relationship and criminal procedural activities - Bibilo, Valentina N. (Journal of the Belarusian State University. Law, 2025)
Social relations are manifested as an objectified activity. Social norms reflect the features of social relations. The criminal procedure legislation sets out models of criminal procedure legal relationship. In reality, only some of them are implemented in a specific criminal case, manifested in the form of criminal procedure activity. Criminal procedure relations and criminal procedure activity are necessary aspects of criminal procedure. Criminal procedure activity ensures the development of the functions of each subject, and criminal procedure legal relationship is the direction of their activity. They do not exist in isolation, they are manifested in a complex. Criminal procedure constitutes their system.